The implement on green building elements toward the performance of existing office building / Abdul Haq Mohamad Yusof - Mohamad Yusof, Abdul Haq (Faculty of Architecture, Planning and Surveying, 2015)
Green building is primary issue in the new era of construction technology. Generally, the green building is considered to be an environmental component, as the green building materials are manufactured from local eco-sources, i.e. environmentally friendly materials, which are then used to make an eco-construction subject to an eco-design that provides a healthy habitat built on the cultural and architectural heritage in construction while ensuring conservation of natural resources. Normally, consideration of green building element has been implemented at early design stage where the green building systems are implemented for the new construction of office building. But, for the implementation of existing office building is rarely. This research aims to improve the performance of the existing office buildings by implementing the green building elements with several objectives which are first is to study the concept of green building, second is to investigate the implementation of green building elements towards the performance of existing building and the third objective is to determine the most preferred element of green building towards the performance of existing office building.